The Origins and Development of Bijeljina in the 16th Century - Handžić, Adem (Prilozi za orijentalnu filologiju, 2017)
On the basis of the cad astral records dating from 16th century, the author explains the origins of Bijeljina, an urban settlement on the northern, flat area of Bosnia. Bijeljina and the Franciscan monastery in it were mentioned in 14th century, obviously being the centre of the homonymous župa. This district finally came under the Turkish suzerainity around 1520. The Turkish records named only the nahiye "Bijeljina", while the main village was named ''Četvrtkovište''; due to the market-day which used to be held on Thursday (četvrtak). Only from the first half of 17th century on, the central age was also named "Bijeljina" (instead of the previous name "Četvrtkovište"). It has also been established that the mentioned monastery (Conventus S. Mariae in Campo) was not situated in Bijeljina itself, but in the neighbouring Koraj. The nahiye of Bijeljina comprised 17 villages in all. In the first half of the 16th century (in 1533) "Četvrtkovište" itself was a small village with 14 households, all of them being the Moslem ones. Otherwise, many of the former inhabitants had fled from the area so the Turks inhabited the district by numerous Vlachs- cattle breeders. The spreading of Islam was rather slow. In the year 1604 the confessional ratio of that nahiye was the following: 686 Christian and 286 Moslem households. The settlement of Bijeljina itself developed slowly, although lying on the important road to Slavonija. In the mentioned year, it was a settlement with only 80 Moslem households. Nevertheless, by 1580 it met the basic requirements of urban development and gained the status of kasaba, that is, the necessary cultural establishments were organized and the market-day established. The fust mosque was built there in the reign of Sultan Suleyman (1520 - 1566). That same year the Kadiluk of Bijeljina was established and, besides the nahiye of Bijeljina, it included the nahiyes of Teo čak and Koraj. Also, in the same year the annual fair was transfered from Koraj, where it had been previously held, to Bijeljina. So, Bijeljina became an administrative-juridical, cultural and economic centre of that lowland. triangle placed between the rivers Sava and Drina.